The role of problem-based learning in developing communication conflict resolving skills among selected non-government organisations in Pakistan - Deep, Sadia (2018)
Communication conflicts among employees of the developing organisations in Pakistan have been one of the major issues over the years. The causes are numerous but the efforts to reduce and resolve these conflicts effectively are found to be rare. The objectives of this case study were to examine the nature of communication conflicts predominant among employees at the workplace, explore the role of culture in communication conflicts, identify the perceptions of employees of in-house training using Problem Based Learning (PBL) approach and finally propose a PBL-based training module for developing conflict resolving skills among employees at the work place in Pakistan. This study adopted a Case Study approach. Using purposeful sampling, it involved forty Non-Governmental Organizations (NGOs) employees from different parts of Pakistan. The data emerged from three instruments involving semi-structured interviews, surveys and observations to examine the nature of communication conflicts among employees and see the impact of PBL training on the soft skills of respondents. Interview and observation data were transcribed and analysed through thematic analysis while the data from the survey was computed through descriptive statistics using Statistical Package for Social Sciences (SPSS). The findings from this study show the existence of different type of communication conflicts among employees in the developing organisations. The result shows the substantial role of PBL in developing conflict resolving skills and other essential soft skills among employees as a whole. The finding concludes that PBL plays an instrumental and effective role towards improving the various soft skills and traits including among employees of an NGO sector.